A single-phase single-stage buck-boost inverter intended for low power alternative energy conversion systems: Analysis, design and experimentation - Pena, Jose C. U. [UNESP]; E Melo, Guilherme de A. [UNESP]; De Brito, Moacyr A. G. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper presents the operational analysis of the single-phase integrated buck-boost inverter. This topology is able to convert the DC input voltage into AC voltage with a high static gain, low harmonic content and acceptable efficiency, all in one single-stage. Main functionality aspects are explained, design procedure, system modeling and control, and also component requirements are detailed. Main simulation results are included, and two prototypes were implemented and experimentally tested, where its results are compared with those corresponding to similar topologies available in literature. © 2012 IEEE.
Keywords: Buck-Boost inverter; integrated inverters; single-phase inverters; single-stage inverters; Ac voltage; Buck boost inverter; Design procedure; Input voltages; Integrated inverter; Low harmonics; Low Power; Operational analysis; Single stage; Single-phase inverters; Single-stage inverters; System modeling and control; Energy conversion; Industrial applications; Topology